Possible drill holes and pseudoborings in obolid shells from the Cambrian/Ordovician boundary beds of Estonia and the uppermost Cambrian of NW Russia. (2nd December 2021) - Vinn, Olev; Holmer, Lars E.; Wilson, Mark A.; Isakar, Mare; Toom, Ursula
ABSTRACT: Rare Oichnus simplex drill holes occur in mature obolid shells from the Cambrian/Ordovician boundary beds of northern Estonia (Iru and Ülgase) and the uppermost Cambrian of NW Russia (Lava River). The drill holes are significantly more common in the central rather than the marginal regions of the obolid valves. Drilling predators attacked Ungula ingrica in the Kallavere Formation and Ungula convexa in the Ladoga Formation. Failed predatory attacks on obolids were relatively common in the latest Cambrian-earliest Tremadocian of Estonia. Presumably drilling predators at Lava River and Iru differed from those at the Ülgase as indicated by significant differences in drill hole sizes at these locations. Most likely some types of worms preyed on obolids in the latest Cambrian-earliest Tremadocian of Estonia and latest Cambrian of NW Russia. The predation rate (6% to 9%) of studied obolids indicates that they likely had an epibenthic life mode. In addition to Oichnus drill holes in the obolids, there are also common pseudoborings caused by mineral dissolution.